2003
DOI: 10.1074/jbc.m212966200
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 as a Cell Cycle-regulated Transcription Factor Facilitating Cyclin A and Cyclin B1 Gene Expression

Abstract: Expression of the Y-box protein YB-1 is increased in proliferating normal and cancer cells, but its role in cell proliferation and cell cycle progression is unclear. We have identified a cell cycle-dependent relocalization of YB-1 from the cytoplasm to the nucleus at the G 1 /S phase transition and demonstrate that both the charged zipper and the cold shock domain are involved in regulating this process. Using cell lines that constitutively overexpress YB-1, we show that nuclear accumulation of YB-1 is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
207
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(223 citation statements)
references
References 56 publications
12
207
1
3
Order By: Relevance
“…This view is supported by recent evidence that shows an accumulation of proteolytically cleaved YB-1 species in various cancer tissues (Sorokin et al, 2005). These truncated YB-1 proteins carry the CSD but lack the C-terminal cytoplasmic retention domain and therefore localize to the cell nucleus (Stenina et al, 2001;Jurchott et al, 2003;. The mechanism by which nuclear YB-1 contributes to oncogenesis is not known but may be related to the transcriptional and chromosomal regulatory activities of nuclear YB-1 (Bader, 2006).…”
mentioning
confidence: 75%
“…This view is supported by recent evidence that shows an accumulation of proteolytically cleaved YB-1 species in various cancer tissues (Sorokin et al, 2005). These truncated YB-1 proteins carry the CSD but lack the C-terminal cytoplasmic retention domain and therefore localize to the cell nucleus (Stenina et al, 2001;Jurchott et al, 2003;. The mechanism by which nuclear YB-1 contributes to oncogenesis is not known but may be related to the transcriptional and chromosomal regulatory activities of nuclear YB-1 (Bader, 2006).…”
mentioning
confidence: 75%
“…Notwithstanding these observations, nuclear translocation of YB1 has been shown to occur in a cell cycle stagedependent fashion, occurring only at the G 1 /S phase boundary, 52 that it is dependent on binding to the splicing factor SRp30c, 53 and as mentioned above, it requires Aktdependent phosphorylation. 46 Rationalization of these separate observations has yet to occur, but an association with cell cycle stage could be a possible link.…”
Section: The Y-box-binding Protein Yb1mentioning
confidence: 96%
“…The YB-1 protein has been previously reported to be predominantly located in the cytoplasm in normal and tumor cells throughout the cell cycle (in association with an anchoring protein in the cytoplasm at a binding site on the C-terminal tail domain), but the protein is known to translocate into the nucleus during the G 1 to S phase transition. 20,21 Zhang et al 22 have further demonstrated that nuclear localization of YB-1 requires wild-type p53.…”
Section: Discussionmentioning
confidence: 99%